Implementing lean: Outcomes from SME case studies - Antony Pearce; Dirk Pons; Thomas Neitzert (Operations Research Perspectives, 2018)
The purpose of this work was to identify critical success factors for lean implementation. It followed two first-time implementations of lean in small to medium-sized enterprises (SMEs). The case studies collectively spanned over four years. It was observed that the real problem with achieving lean success was not management commitment but their ignorance of what they should commit to, hence a knowledge problem. This paper provides new insights into the role of knowledge as a causal factor in the successful implementation of lean and especially in organisations with limited resources. For practitioners, management knowledge needs active consideration in the implementation phase. Management knowledge is particularly significant in SME implementations due to their resource constraints. Researchers still need to define the success factors more explicitly, including the specific management commitments.
Keywords: 330; Lean; Management; Knowledge; Production; Case study; SME